Analysis of Arabic Language Questions Based on Higher Order Thinking Skills (HOTS) in the Arabic Language Book for Class XI Ministry of Religion - Farros, Aathifah Al (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2024)
This research aims to reveal the content of higher order thinking skills (HOTS) in the Arabic language textbook for the classroom. This research uses a qualitative descriptive approach with content analysis methods. The data analysis technique used is Miles and Huberman's model which includes four stages: data collection, data reduction, data presentation, and drawing conclusions. The results of the research that were described concluded that 1) the details of the content containing higher order thinking skills (HOTS) in the Arabic language book for the semester consist of a mixture of different cognitive levels, 2) the amount of higher order thinking skills (HOTS) content in the test consists of the first lesson failure. Of the 54% LOTS content and 46% HOTS content, then in the test Derasi Al-Tassani ad failure consists of 54% LOTS load and 46% HOTS load. Keywords: Analyze, HOTS, Evaluation, Arabic Language